Analisis faktor yang mempengaruhi kinerja UKM di pasar internasional - Aglis Andhita Hatmawan (Jurnal Ekonomi Modernisasi, 2020)
Small and medium enterprises (SMEs) are currently important players in international trade. Commitment from business actors and wider networks are required to not only penetrate the international market but also to survive and compete at the national and international levels. This study aims to analyze entrepreneurial orientation, network capabilities, and innovation on the performance of SMEs in the international market. This study used a survey method by giving questionnaires and interviews to 75 manufacturing SMEs in the district and city of Madiun. The results of this study indicate that all entrepreneurial orientation variables, network capability, and innovation have positive and significant effects on the performance of SMEs in the international market. This study contributes to the internationalization of SME's literature by analyzing the influence of entrepreneurship orientation, networking capabilities, and innovation on SME performance in international markets, especially for manufacturing companies.